Operationalizing the Nexus Approach: Insights From the SIM4NEXUS Project - Ramos, Eunice Pereira; Kofinas, Dimitris; Sundin, Caroline; Brouwer, Floor; Laspidou, Chrysi (Frontiers in Environmental Science, 2022)
Over the past decades, the understanding and assessment of cross-systems interactions have gained momentum in research and policy-support. As such, scientific literature on Nexus assessment methods and applications continues to grow, followed by numerous state-of-the-art reviews. Among the flexibility and variety of Nexus approaches, comprehensive, transferable and accessible methodologies with operational potential are missing. To address this gap, we introduce the SIM4NEXUS approach, which emerged from twelve test cases. Fledged from practice, the approach is a unique output in the Nexus research field. It is informed by the development of twelve case studies, which differ in spatial scope, socioeconomic and biophysical contexts, and Nexus challenges. The studies were conducted under similar conditions (e.g., timeframe and multidisciplinary teams of experts and dialogues with practitioners from policy and business). We find that transdisciplinarity and the integration of qualitative and quantitative methods are vital elements in Nexus assessments for policy support. Additionally, we also propose steps to advance Nexus assessments: 1) integration of the policy cycle in research (including monitoring and evaluation, and offer support during the implementation process), 2) multidisciplinary collaboration with different levels of engagement and financial support, 3) inclusion of ecosystems and other relevant dimensions (e.g., health) in the Nexus. Ultimately, the SIM4NEXUS approach provides practice-based guidance on conducting a Nexus assessment, and we recommend it for future Nexus assessments by the research community, institutions, and private actors.